Róža Domašcyna’s Poetical Project between Folklore and Modernity - Kledzik, Emilia (Poznańskie Studia Slawistyczne, 2015)
Poetical project by Sorbian poet Róža Domašcyna fits into the category of „minor literature”, coined by F. Guattari and G. Deleuze in 1975. Despite its inevitably political, ecological and ideological local connotations, it is rooted in the experience of modernity, still unpopular among the contemporary Sorbian writers. Its main topics are: the devastation of Lusatian environment, erotic and cultural hybridity. Domašcyna uses the hybrid nature of Sorbian identity to create an post-modern subject, conscious of the non-transparent nature of language. The result is an original poetry, which suits the current comparative and postcolonial categories of interpretation.